Phase 1B trial of Nab-paclitaxel plus gemcitabine, capecitabine, and cisplatin (PAXG regimen) in patients with unresectable or borderline resectable pancreatic adenocarcinoma - Reni, Michele (Br J Cancer, 2016)
BACKGROUND: Nab-paclitaxel–gemcitabine combination significantly improved overall survival over gemcitabine in metastatic pancreatic adenocarcinoma. A phase 1b trial was performed (ClinicalTrials.gov number, NCT01730222) to determine the recommended phase 2 dose (RP2D) of nab-paclitaxel in combination with cisplatin, capecitabine, and gemcitabine at fixed dose (800, 30, and 1250 mg m(−2) every 2 weeks, respectively; PAXG regimen). METHODS: Nab-paclitaxel doses were escalated from 100 (level one) to 125 (level two) and 150 mg m(−2) (level three) every 2 weeks in cohorts of 3–6 patients with pathologically confirmed unresectable or borderline resectable pancreatic adenocarcinoma. RESULTS: Between Dec 2012 and Apr 2014, 24 patients were enroled (3 at level one, 5 at level two, 16 at level three) and received 117 cycles of PAXG. No dose-limiting toxicity occurred and level three was the RP2D. At this dose, nab-paclitaxel dose-intensity was 91%. Worse per patient grade 3/4 toxicity were neutropenia 25/31% fatigue 19% anaemia and hand-foot syndrome 12%, nausea 6%, and febrile neutropenia 6%. A partial response (PR) was observed in 16 (67%) and stable disease (SD) in 8 patients (33%). Among 21 patients with a baseline positive positron emission tomography (PET) scan, a complete metabolic response was observed in 9 (43%), PR in 10 (48%), SD in 2. CA19-9 decreased by ⩾49% in all the 19 patients with elevated basal value. Six patients were resected after chemotherapy. Progression-free survival at 6 months (PFS-6) was 96%. CONCLUSIONS: The RP2D of nab-paclitaxel in the PAXG regimen was 150 mg m(−2) every 2 weeks. The preliminary results are promising and warrant further exploration.